Frameworks for mitigating the risk of waterborne diarrheal diseases: A scoping review. - Chisala D Meki; Esper J Ncube; Kuku Voyi (PLoS ONE)
Background Diarrhea is one of the major cause of death and morbidity around the world. Objectives This scoping review summarizes existing frameworks that aim to mitigate the risks of waterborne diarrheal diseases and describe the strengths and weaknesses of these frameworks. Eligibility criteria Published frameworks designed to mitigate the risks of waterborne diarrheal diseases. Frameworks published in English, from around the world and published since inception to date. Sources of evidence PubMed, Scopus, Web of Science, Google Scholar, Google Free Search, organization websites and reference lists of identified sources. Charting methods Data were charted using the Joanna Briggs Institute tool. Results were summarized and described narratively. A criterion to score the strengths and weaknesses of the included frameworks was also developed. Results Five frameworks were identified including: the hygiene improvement framework, community led total sanitation, global action plan for pneumonia and diarrhea, participatory hygiene and sanitation transformation, and sanitation and family education. These frameworks shared several common components, including identification of problems and risk factors, identification and implementation of interventions, and evaluation and monitoring. The frameworks had several interventions including different infrastructure, health promotion and education, enabling environment and clinical treatments. Most of the frameworks included health promotion and education. All the frameworks were strengthened by including strategies for implementing and delivering intervention, human resource aspect, community involvement, monitoring, and evaluation. The main weakness included not having components for collecting, storing, and transferring electronic data and the frameworks not being specifically for mitigating waterborne diarrheal diseases. In addition, the identified frameworks were found to be effective in mitigating the risk of diarrhea diseases among other health effects. Conclusions Existing frameworks should be updated specifically for mitigating waterborne diarrheal diseases that includes the strengths and addresses weaknesses of reviewed frameworks.